Nanostructured Copolymer Gels for dsDNA Separation by Capillary Electrophoresis - Wan, Fen (2008)
Pluronics copolymers are triblock copolymers of poly(ethylene oxide)-poly(propylene oxide)-poly(ethylene oxide) and are able to form many different ordered nanostructures at appropriate polymer concentrations and temperatures in selective solvents. These nano-structured ‘gels’ showed desirable criteria when used as DNA separation media, especially in microchip electrophoresis, including dynamic coating ability and viscosity switchable property. A ternary system of F127 (E(99)P(69)E(99))/TBE buffer/1-butanol was selected as a model system to test the sieving performance of different nanostructures in separating dsDNA by capillary electrophoresis. The lattice structures were determined by small-angle x-ray scattering with quasi-lattice crystal parameters being calculated according to the x-ray scattering data. Viscosity measurements showed the sol-gel transition phenomena. In addition to the cubic structure, successful electrophoretic separation of dsDNA in 2-D hexagonal packed cylinders was achieved. Results showed that without further optimization, ΦX174 DNA-Hae III digest was well separated within 15 minutes in a 7-cm separation channel, by using F127/TBE/1-butanol gel with a 2-D hexagonal structure. A mechanism for DNA separations by those gels with both hydrophilic and hydrophobic domains is discussed.